2005
DOI: 10.1007/s00425-005-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of cell wall invertases in developing endosperm of maize

Abstract: We show here that the total invertase activity in developing seeds of maize is due to two cell wall invertase (CWI) genes, Incw1 and Incw2 (Mn1). Our previous results have shown that loss-of-function mutations at the Mn1 locus lead to the miniature-1 (mn1) seed phenotype, marked by a loss of >70% of seed weight at maturity. The mn1 seed mutant is, however, non-lethal presumably because it retains a residual low level, approximately 1%, of the total CWI activity relative to the Mn1 endosperm throughout seed dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 37 publications
2
92
0
Order By: Relevance
“…The mn1-89 allele encodes normal or higher levels of Incw2 RNA compared to the wild type, but exceedingly low levels, ~ 6% of the Mn1, of the INCW2 protein and enzyme activity (Cheng et al, 1996). More importantly for the studies here, genetic analyses showed that the mn1-89 allele is semi-dominant in seed phenotype (Cheng et al, 1996) when crossed to the standard null allele, mn1-1, which has approximately ~1% of the wild type levels of invertase activity encoded by the non-allelic gene, Inc1, a paralog of the Mn1 locus (Chourey et al, 2006). The reciprocal hybrids from such crosses yield gene-dose dependent invertase activity levels of ~4 and 2% encoded by two and one mn1-89 alleles, respectively, present in the triploid endosperms.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The mn1-89 allele encodes normal or higher levels of Incw2 RNA compared to the wild type, but exceedingly low levels, ~ 6% of the Mn1, of the INCW2 protein and enzyme activity (Cheng et al, 1996). More importantly for the studies here, genetic analyses showed that the mn1-89 allele is semi-dominant in seed phenotype (Cheng et al, 1996) when crossed to the standard null allele, mn1-1, which has approximately ~1% of the wild type levels of invertase activity encoded by the non-allelic gene, Inc1, a paralog of the Mn1 locus (Chourey et al, 2006). The reciprocal hybrids from such crosses yield gene-dose dependent invertase activity levels of ~4 and 2% encoded by two and one mn1-89 alleles, respectively, present in the triploid endosperms.…”
Section: Introductionmentioning
confidence: 59%
“…3). It is noteworthy that there is a discrepancy between protein and enzyme activity levels and Incw2 transcript levels in Mn1 and mn1 endosperms (Chourey et al, 2006), since high RNA level in the homozygous mn1-89 mutant results in only ~6 % of the Mn1 invertase activity (Cheng et al, 1996). It has been suggested that a large proportion of INCW2 is dispensable without a significant change in seed phenotype (Cheng et al, 1996).…”
Section: Caryopsis Dry Mass and Zmincw2 Transcript Level Correlate Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CWINs are central to phloem unloading and carbon partitioning, especially in cellular sites lacking symplasmic (plasmodesmal) connections (Patrick and Offler, 2001;Weschke et al, 2003). A positive correlation between CWIN activity and seed development has been observed in maize (Zea mays; Cheng et al, 1996;Vilhar et al, 2002;Chourey et al, 2006), faba bean (Vicia faba; Weber et al, 1995Weber et al, , 1996, barley (Hordeum vulgare; Weschke et al, 2003;Sreenivasulu et al, 2004), rice (Oryza sativa; Hirose et al, 2002;Wang et al, 2008), and tomato (Solanum lycopersicum; Zanor et al, 2009). With an exception in tobacco (Nicotiana tabacum; Tomlinson et al, 2004), high and low Glc-to-Suc ratios generally favor cell division or promote cell differentiation, respectively, during seed development (for review, see Weber et al, 2005).…”
mentioning
confidence: 99%
“…In addition, Ivr2 was found to be specifically induced under water stress (Kim et al, 2000a;Trouverie et al, 2003). Incw1 and Incw2 expression showed significant spatial and temporal heterogeneity in the developing endosperm (Chourey et al, 2006). Three genes encode maize sucrose synthase, including Sh1, Sus1, and Sus2 (Werr et al, 1985;Gupta et al, 1988;Carlson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%